Exploring the Dynamic Nexus between Indonesian Economic Forces and Islamic Banking Financial Performance - Nora Ria Retnasih (Journal of Islamic Economics and Finance Studies, 2023)
World economic uncertainty during the pandemic resulted in a decline in overall economic activity. This has an impact on the financial performance of Islamic banks, especially those related to business and consumer financing. Most customers face financial difficulties and ultimately have the potential for increased credit risk. So, there is a mutual connection between macroeconomic indicators and the financial performance of Islamic banks. This research aims to measure the magnitude of the influence of economic variables on the financial performance of Indonesian Sharia Banking for the period 2020 quarter 1 to 2022 quarter 4. The method used in this quantitative research is Panel Vector Autoregressive (PVAR). The research results show that the exchange rate significantly affects Islamic banks' financial performance. In the long term, exchange rate shocks positively impact the FDR and NPF variables, while the ROA and CAR variables give a negative response. The exchange rate also makes the largest contribution to all financial performance variables compared to interest rates and the consumer price index. The implication is for policymakers to always maintain domestic economic stability, especially the exchange rate. Exchange rate stability reflects price stability as measured by inflation and will have an impact on other economic indicators.   Ketidakpastian ekonomi dunia selama pandemi mengakibatkan penurunan aktivitas ekonomi secara keseluruhan. Hal ini berdampak pada kinerja keuangan bank syariah terutama yang terkait dengan pembiayaan bisnis dan konsumen.  Sebagian besar nasabah menghadapi kesulitan keuangan dan pada akhirnya berpotensi pada peningkatan resiko kredit. Sehingga terdapat keterikatan satu sama lain antara indicator perekonomian makro dan kinerja keuangan bank syariah. Penelitian ini bertujuan untuk mengukur besarnya pengaruh variabel ekonomi terhadap kinerja keuangan Perbankan Syariah Indonesia periode tahun 2020 triwulan 1 sampai dengan tahun 2022 triwulan 4. Metode yang digunakan dalam penelitian kuantitatif ini adalah Panel Vector Autoregressive (PVAR). Hasil penelitian menunjukkan bahwa nilai tukar berpengaruh signifikan terhadap kinerja keuangan bank syariah. Dalam jangka panjang guncangan nilai tukar memberikan dampak positif terhadap variabel FDR dan NPF, sedangkan variabel ROA dan CAR memberikan respon negatif. Selain itu, nilai tukar juga memberikan kontribusi paling besar terhadap seluruh variabel kinerja keuangan dibandingkan tingkat suku bunga dan indeks harga konsumen. Implikasinya bagi pengambil kebijakan untuk selalu menjaga stabilitas perekonomian dalam negeri, khususnya nilai tukar. Stabilitas nilai tukar mencerminkan stabilitas harga yang diukur dengan inflasi dan akan berdampak pada indikator perekonomian lainnya.